Narrative Review: Implementasi Distribusi Obat yang Baik di Pedagang Besar Farmasi - Mustaqimah Mustaqimah; Rina Saputri; Ali Rakhman Hakim (Jurnal Surya Medika (JSM), 2021)
Distribution of pharmaceutical products from the pharmaceutical industry before reaching the pharmacy service point must be through wholesale. Good distribution practice methods are a set of standardized routine working methods, which ensure the quality, safety, and efficacy of pharmaceutical products remain intact from the very beginning to the end of the expiration period. Good distribution practice methods must be implemented by all wholesale in Indonesia so that wholesale operations can run effectively and efficiently. All pharmaceutical wholesalers must have standard operating procedures, personnel with integrity, and a good documentation system.